University lecturers’ perceptions on digital transformation and knowledge management for teaching innovation - Songkram, Noawanit; Shidiq, Galih Albarra; Winarto; Taweejamsup, Suphasit; Songkram, Nutthakorn (My University, 2026)
This study used the qualitative design to investigate the perceptions of 33 university lecturers through semi-structured interviews and observations conducted after a professional development program in Indonesia. Thematic analysis discovered three interconnected dimensions shaping innovation in teaching: (1) supportive institutional environments that promote responsible behaviour, teamwork, and collaboration; (2) acquisition and application of new knowledge through digital tools and collegial learning; and (3) integration of technological innovation to improve teaching efficiency, creativity, and multidisciplinary engagement. The findings indicate that effective knowledge management enhances lecturers’ ability to adapt digital pedagogies, share expertise, and sustain innovation practices. The implications of this study include developing professional learning communities, improving digital literacy programs, and aligning institutional policies to support innovation in teaching. These insights extend global understanding of how universities in emerging contexts can strategically integrate technology and knowledge management to advance educational innovation.
Keywords: digital literacy; Digital transformation; higher education; innovation in teaching; knowledge management